tekst/Tekst (Berchem : UBICUMQUE vzw)
Broucke, Koen ; Declercq, Christophe ; Genard, Pieter ; Hautekiet, Peter ; Lagrange, Thierry ; Meester, Oscar ; Nolens, David ; Raes, Leo ; Van Mullem, Jean-Francois ; Verhoeven, Thibaut ; Verschuren, Jo
TEKST/TEKST 1: Diepe Putten ; TEKST/TEKST 2: Traag zijn, de meesters ; TEKST/TEKST 3: De Grenzen van de poedel ; TEKST/TEKST 4: Wolven ; TEKST/TEKST 5: Boezems ; buiten reeks : Henrietje Tuf-Tuf
tijdschrift